PENGEMBANGAN MODUL PETUNJUK PRAKTIKUM IPA BERBASIS LEARNING CYCLE UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV SEKOLAH DASAR - Riyanto Riyanto; Mega Puspita Sari (Prodi PGSD Universitas PGRI Ronggolawe, 2024)
This development research uses the 4D development model with 4 stages consisting of defining, designing, developing, and disseminating with the research objectives are: (1) to determine the feasibility of the Learning Cycle-based science practicum instruction module for grade 4 elementary schools; (2) to determine the practicality of the Learning Cycle-based science practicum instruction module for grade 4 elementary schools; (3) to determine the effectiveness of the Learning Cycle-based science practicum instruction module for grade 4 elementary schools. Based on the results of the research that has been done, the percentage of module feasibility obtained through expert validation results is 97.9% with very good criteria; the percentage of module practicality obtained through the results of learning implementation, teacher response questionnaires, and student response questionnaires is 96.4% with very practical criteria; and the percentage of media effectiveness obtained through student test results with an average n gain value of 89 and declared effective. So based on some of the results that have been presented, the research on the development of a Learning Cycle-based science practicum guide module for grade elementary